SHUKUR KHOLMIRZAEV’S LIFE AND CAREER (Web of Teachers: Inderscience Research, 2024)
The author of this article is a famous writer of Surkhandarya Shukur Kholmirzayev's work and love of country in his works, about love of country and his works talk about art and literary ideas.